A Public Health Approach to Orofacial Pain - Sujay A. J. Mehta (Journal of the California Dental Association, 2025)
Background Orofacial pain including musculoskeletal pains frequently called temporomandibular disorders poses a significant public health challenge. Chronic pains lasting greater than three months have significant impact on people’s ability to communicate, eat, drink, express emotion and be intimate with ongoing pain. The establishment and recognition of orofacial pain as a specialty encourages further collaboration across various disciplines, improving education and training specific to the recognition and management of complex mouth and face pains and further research at various levels to improve patient care.Types of Studies Reviewed A narrative review offers a public health summary analysis of information and data, the education and awareness of scientific knowledge, and ensuring appropriate care is offered at the community and population level. Historic challenges specific to TMD have included a variety of terms and theories as to mechanisms of action, poorly coordinated care across medicine and dentistry, lack of access to care with associated financial burden in a primarily private payer model of care, and a delay in communicating evidence base to clinicians.Results and Practical Implications The recent recognition of orofacial pain as a specialty coupled with a holistic definition to oral health and improved understanding to the widest scope of oral diseases reinforces the need for a public health approach to addressing multiple challenges in the care of individuals suffering from various types of orofacial pains.